1992
DOI: 10.2175/wer.64.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Odor control research at the Montgomery County Regional Composting Facility

Abstract: Odor control has been an important component of the operation of the Montgomery County Regional Composting Facility. After several facility improvements, which greatly reduced off-site odors, the discharge of compost process air remained the greatest source of odor impacts on the surrounding community. Thus, the WSSC assembled a research team to investigate methods of improving odor control treatment for the process air. The research team developed bench-scale tests and gas chromatographic methods that provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…Generally, composts containing biosolids had greater concentration and types of reduced sulfur compounds than non-biosolids composts. The presence of reduced sulfur compounds in biosolids compost is consistent with previous reports from the U.S. (Hentz et al, 1992) and Europe (Van Durme et al,1992). Reduced sulfur compounds have also been found in association with livestock operations and composted manure (O'Neill and Phillips, 1992).…”
Section: Odorant Characteristics Of Composts Under Studysupporting
confidence: 90%
“…Generally, composts containing biosolids had greater concentration and types of reduced sulfur compounds than non-biosolids composts. The presence of reduced sulfur compounds in biosolids compost is consistent with previous reports from the U.S. (Hentz et al, 1992) and Europe (Van Durme et al,1992). Reduced sulfur compounds have also been found in association with livestock operations and composted manure (O'Neill and Phillips, 1992).…”
Section: Odorant Characteristics Of Composts Under Studysupporting
confidence: 90%
“…When water was used alone, odor reductions were less than 50%. The addition of a surfactant (liquid, unscented Tide laundry detergent), as tested by other researchers (Van DurmezyxwvutsrqponmlkjihgfedcbaZYXWVUTSRQPONMLKJIHGFEDCBA et al, 1990, andHentz et al, 1990), did not improve the performance. zyxwvutsrqponmlkjihgfedcbaZYXWVUTSRQPONMLKJIHGFED Reactive organic gases.…”
Section: Test Resultsmentioning
confidence: 87%
“…Previous evaluations and adsorptive/oxidative dry-media pilot testing performed by the Solids Technology and Resource Recovery Division of the City of Los Angeles indicated that chemical wet scrubbing should be evaluated for emissions control at the Hyperion Treatment Plant's (HTP) Wet Cake Storage Facility (Duffee et al, 1989, andSereno et al, 1990). Literature searches indicated good success with multistage wet scrubbing in controlling emissions from municipal sewage sludge composting operations (Hentz et al, 1990, andVan Durme et al, 1990). Based on these investigations, a pilot test program to investigate the effectiveness of multistage packed tower technology was developed.…”
mentioning
confidence: 99%
“…Hydrogen Peroxide, Chlorine Dioxide, along w ith sodium hypochlorite (NaOCl) at various pHs and other oxidizing agents w ere tested. Nothing removed DMDS nearly as w ell as NaOCl (Hentz et al 1992), and it reacted best at a pH of 6.5 w hich is the range of pH in w hich hypochlorous acid formation is maximized. The scrubber had the capability to adjust the pH of the bleach solution w ith sulfuric acid, but before this test, close control of the pH w as not exercised.…”
Section: Odor Control and Research Needsmentioning
confidence: 97%